Thermal stability of soil organic carbon subjected to water erosion as a function of edaphic factors - Li, Zhongwu; Xiao, Linhui; Deng, Chuxiong; Yuan, Zaijian; Liang, Chen; Xiong, Qian; Li, Zeting; Nie, Xiaodong (International journal of sediment research, 2022)
The stability of soil organic carbon (SOC), as it relates to resistance to decomposition, is important for greenhouse gas emission and climate change. However, the SOC stabilization and its related influencing factors subjected to water erosion remain uncertain. The objective of the current study was to determine the SOC stability under long-term water erosion and to investigate the link between SOC stability and edaphic factors. Soil samples from eroded, depositional, and control sites in a closed watershed in subtropical China were collected. The SOC concentration, carbon functional groups, soil physicochemical properties, and thermal stability of SOC were determined. The study results showed that the primary component of the SOC functional groups was O-alkyl carbon (reached 40%), and its proportion has no significant difference among different sites. The TG-T50 (the temperature at which 50% of the soil organic matter is lost) values indicated that the SOC thermal stability in the eroded topsoil was higher than that of the deposited topsoil. The carbon functional groups were lack of relation with SOC thermal stability (p > 0.05). However, the TG-T50 was significantly positively correlated with the cation exchange capacity and silt, but remarkably negatively correlated with SOC, dissolved organic carbon, total nitrogen, sand, clay, pH, aluminum, specific surface area, and iron oxides. These results indicated that the edaphic factors, which were strongly affected by micro-environment, are the main factors affecting thermal stability of organic carbon. The SOC stabilization under the effects of long-term water erosion should be addressed from the perspective of the ecosystem. •The main component of soil organic carbon chemical composition was O-alkyl carbon.•The eroded SOC was more stable than the deposited SOC on the surface soil.•Stability of SOC is governed by edaphic factors instead of chemical composition.